Rajasthan, India : An Assessment of the Mid-Day Meal Scheme in Chittorgarh District - Cheriyan, George (World Bank, Washington, DC, 2016)
The current initiative was one of six pilot projects launched by the South Asia Sustainable Development Department of the World Bank aimed at the application of specific social accountability tools in different contexts of service delivery through the trust fund for Capacity Building and Piloting of Social Accountability Initiatives for Community Driven Development in South Asia. This note summarizes the findings, processes, concerns, and lessons learned from the Rajasthan pilot.